COVID-19–Considerations for the Female Athlete - Bruinvels, Georgie; Lewis, Nathan A.; Blagrove, Richard C.; Scott, Dawn; Simpson, Richard J.; Baggish, Aaron L.; Rogers, John P.; Ackerman, Kathryn E.; Pedlar, Charles R. (Frontiers in Sports and Active Living, 2021)
The SARS CoV-2 virus (COVID-19) caused the whole sporting calendar to be paused. As we embark on the challenge of navigating through the return to play (RTP) process, there is a necessity to consider the needs of all athletes. This commentary specifically considers recommendations and requirements for the female athlete during and following the COVID-19 pandemic, however, it will be relevant for any similar future scenarios that may present. It is important to acknowledge that there remain many unknowns surrounding COVID-19 and the female athlete both in the short- and long-term.